2019
DOI: 10.1002/we.2404
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine reliability data review and impacts on levelised cost of energy

Abstract: Reliability is critical to the design, operation, maintenance, and performance assessment and improvement of wind turbines (WTs). This paper systematically reviews publicly available reliability data for both onshore and offshore WTs and investigates the impacts of reliability on the cost of energy. WT failure rates and downtimes, broken down by subassembly, are collated from 18 publicly available databases including over 18 000 WTs, corresponding to over 90 000 turbine‐years. The data are classified based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
138
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 180 publications
(166 citation statements)
references
References 42 publications
0
138
0
Order By: Relevance
“…When simulating the operation of a new OWT, the turbine designers and developers (experts) can specify the likelihood that a component's reliability gets a value of its reliability in a reference reliability database. In addition, there are reviews on existing wind turbine reliability databases, 12,35 which investigate a large population of wind turbines and provide averages and ranges of failure rate and downtime. Data obtained from this large population can be used to estimate the reliability data uncertainty and probabilistic reliability matrices P f and P d .…”
Section: Component Reliability Data Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…When simulating the operation of a new OWT, the turbine designers and developers (experts) can specify the likelihood that a component's reliability gets a value of its reliability in a reference reliability database. In addition, there are reviews on existing wind turbine reliability databases, 12,35 which investigate a large population of wind turbines and provide averages and ranges of failure rate and downtime. Data obtained from this large population can be used to estimate the reliability data uncertainty and probabilistic reliability matrices P f and P d .…”
Section: Component Reliability Data Uncertaintymentioning
confidence: 99%
“…Existing operational simulation models often assume a fixed failure rate or failure probability for the wind turbine. In the literature, reliability data are often collected and analysed for the turbines that have been operating for several years, 11,12 whereas the operational simulation needs to model and predict the operation of future OWTs. The lack of data problem has been an issue in the research community, which has been mentioned in previous studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Power coefficient C p (λ ,β ) is given by the standard equation as in ( From [1], for a range of values of the pitch angle β, the characteristic function C P (λ, β) vs λ, is illustrated in Fig.1. From the graph it is found that C Pmax =0.36, for β = 2º and λ=9.6.…”
Section: Mathematical Modelling Of Wecsmentioning
confidence: 99%
“…With remarkable advancements in power electronics, wind energy sector grows rapidly and becomes equally competitive to other types of renewable sources and also due to its reliability, cost effectiveness and quality of power [1]- [2]. Wind energy conversion system (WECS) consists of either horizontal axis or vertical axis wind turbines, either doubly fed induction generator (DFIG) or permanent magnet synchronous generator (PMSG) generators, control system, and interconnection apparatus [3].…”
Section: Introductionmentioning
confidence: 99%